Estimating The Term Structure of Interest Rates: The Swiss Case - Iwan Meier (Swiss National Bank, Study Center Gerzensee, 1999)
Parametric estimation approaches are widely by central banks as they produce smooth term structures with relatively few parameters. In the paper I implement the Nelson and Siegel (1987) model for Switzerland. The estimations use daily observations of Swiss government bonds from January 1994 to July 1998. To overcome the lack of sufficient data in the very short run, the 1-month and 1-year Euromarket rate are added. The knowledge of the dependencies of the term structure from the possible parameter constellations is used to calibrate the model for the Swiss market. The results show that the parameters are stable over time. The smooth shape and the stability over time make it a valuable tool for monetary policy.
Keywords: E43; 330; Term structure of interest rates; Interpolation